Reading for thinking - Flemming, Laraine E. (Cencage Learning, 2015)
Through a combination of easy-to-understand explanations, high-interest readings, and a carefully designed chapter sequence, Laraine Flemming's Reading for Thinking, this title takes the mystery out of critical reading for developmental students.